Feasibility and Pathologic Outcomes of Peripheral Lung Vascular Targeted Photodynamic Therapy in a Normal Porcine Lung ModelTake-home Points - Jason Beattie; Mario Ghosn; Kwanghee Kim; Raymond Parrish; Jie Chen; Stephen B. Solomon; Sebastien Monette; Christopher Cheleuitte-Nieves; Reza Bergemann; Mohit Chawla; Bryan C. Husta; Or Kalchiem-Dekel; et al. (CHEST Pulmonary)
Background: Bronchoscopic ablation of tumors in the lung periphery may offer unique advantages over traditional surgical resection or radiation. Bronchoscopic vascular targeted photodynamic therapy (VTP) is a second-generation photodynamic therapy that avoids excessive tissue extravasation and is rapidly cleared from the circulation. These advantages avoid prolonged photosensitivity and allow for infusion and illumination within the same procedure. The treatment effect and systemic inflammatory response precipitated by VTP may prove advantageous for anticancer effects, alone or in combination with immune oncology therapies. Research Question: A baseline understanding of this modality’s effect on lung parenchyma is needed to provide further guidance toward its potential as a method for bronchoscopic ablation of lung tumors. We report on our initial experimentation with bronchoscopic lung VTP in normal pigs. Study Design and Methods: We performed conventional bronchoscopy for deployment of optical fibers into the peripheral lung. We then infused the photosensitizer WST11 after which we immediately performed illumination of the optical fibers. Results: Our results across 13 pigs with varied survival (between 1 day and 30 days) demonstrate initial feasibility and reasonable safety. Posttreatment radiology and pathology support measurable ablation fields and expected post-VTP changes. Interpretation: Our preclinical evidence provides early rationale for the study of safety and feasibility of bronchoscopic VTP ablation of peripheral lung cancers in humans.